LEGAL PROTECTION OF TRADERS IN DIGITAL ASSET INVESTMENT THROUGH PRIVATE DIGITAL CURRENCY IN INDONESIA - Adi Mas Sanjaya Putra; I Wayan Novy Purwanto (POLICY, LAW, NOTARY AND REGULATORY ISSUES, 2023)
This study examines the government's response to protect traders engaged in digital asset transactions in Indonesia and analyzes the legal protection available to traders in case of disputes with exchanges. The research employs a normative legal method that investigates relevant rules, norms, and doctrines. The findings indicate that the government has implemented preventive legal protection measures through the Commodity Futures Supervisor, as stipulated in the Decree of the Minister of Industry and Trade Number: 86/Mpp/Kep/3/2001, which outlines the organizational structure of the Ministry of Industry and Trade, specifically Article 1112. Furthermore, traders have access to repressive legal remedies, such as filing a lawsuit under Article 1365 of the Civil Code for the recovery of their rights (compensation) and initiating a default suit according to Article 1243 of the Civil Code in the district court situated in the trader's jurisdiction. Additionally, non-litigation settlements serve as an alternative option available to traders.